Answer:
the denominator would be 1
Step-by-step explanation:
because 5 and 5/1 are equivalent
The length of the sides are 2.24, 4.24 and 4.12 units while the slope are 0.5, -1 and -4.
<h3>Linear equation</h3>
A linear equation is in the form:
y = mx + b
where y, x are variables, m is the rate of change and b is the initial value of y.
For RS:
For RT:
For ST:
The length of the sides are 2.24, 4.24 and 4.12 units while the slope are 0.5, -1 and -4.
Find out more on linear equation at: brainly.com/question/14323743
The correct question is:
Suppose x = c1e^(-t) + c2e^(3t) a solution to x''- 2x - 3x = 0 by substituting it into the differential equation. (Enter the terms in the order given. Enter c1 as c1 and c2 as c2.)
Answer:
x = c1e^(-t) + c2e^(3t)
is a solution to the differential equation
x''- 2x' - 3x = 0
Step-by-step explanation:
We need to verify that
x = c1e^(-t) + c2e^(3t)
is a solution to the differential equation
x''- 2x' - 3x = 0
We differentiate
x = c1e^(-t) + c2e^(3t)
twice in succession, and substitute the values of x, x', and x'' into the differential equation
x''- 2x' - 3x = 0
and see if it is satisfied.
Let us do that.
x = c1e^(-t) + c2e^(3t)
x' = -c1e^(-t) + 3c2e^(3t)
x'' = c1e^(-t) + 9c2e^(3t)
Now,
x''- 2x' - 3x = [c1e^(-t) + 9c2e^(3t)] - 2[-c1e^(-t) + 3c2e^(3t)] - 3[c1e^(-t) + c2e^(3t)]
= (1 + 2 - 3)c1e^(-t) + (9 - 6 - 3)c2e^(3t)
= 0
Therefore, the differential equation is satisfied, and hence, x is a solution.
Answer:
h-15=42 ~~~~ Brainliest would be nice :') thank u!
Step-by-step explanation:
Answer:
$8.2
Step-by-step explanation:
The final price of the coat = $45 -0.2 * $45 = $36
The final price of the suit = $95 − 0.3 * $95 = $66.5
sarosh's commission = 0.08 * ( $36 + $66 ) = $8.2